2016
DOI: 10.1039/c6ta02276f
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Fenton-catalytic efficiency by highly accessible active sites on dandelion-like copper–aluminum–silica nanospheres for water purification

Abstract: A novel Fenton catalyst consisting of dandelion-like copper-aluminum-silica nanospheres (DCAS Ns) was successfully prepared via a hydrothermal process for the first time. This catalyst exhibited exceptionally high activity and stability for the degradation and mineralization of various refractory pollutants, as demonstrated with phenol, pharmaceuticals, pesticides, dyes and endocrine disrupting chemicals at neutral pH. The reaction rate was 5.2-13.4 times higher than that of the conventional Fenton catalysts. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(37 citation statements)
references
References 41 publications
2
34
0
Order By: Relevance
“…18 These problems have seriously hindered the application of heterogeneous Fenton catalysts. 20 Our former research on Cu-based heterogeneous Fenton-like systems [19][20][21] has shown that these problems could be overcome by forming s-Cu 2+ -complexes on the surface of catalysts for aromatic pollutant degradation. On this basis, we developed a series of metal Cu-organic catalysts to construct the C-O-Cu bonding bridge and induce the generation of dual-reaction-centers (DRCs) with electron-rich and electron-deficient areas, [22][23][24] which resulted in a significant increase in the activity of the catalyst and a great increase in the utilization efficiency of H 2 O 2 (up to B90%).…”
Section: Introductionmentioning
confidence: 99%
“…18 These problems have seriously hindered the application of heterogeneous Fenton catalysts. 20 Our former research on Cu-based heterogeneous Fenton-like systems [19][20][21] has shown that these problems could be overcome by forming s-Cu 2+ -complexes on the surface of catalysts for aromatic pollutant degradation. On this basis, we developed a series of metal Cu-organic catalysts to construct the C-O-Cu bonding bridge and induce the generation of dual-reaction-centers (DRCs) with electron-rich and electron-deficient areas, [22][23][24] which resulted in a significant increase in the activity of the catalyst and a great increase in the utilization efficiency of H 2 O 2 (up to B90%).…”
Section: Introductionmentioning
confidence: 99%
“…† d-TiCuAl-SiO 2 Ns were synthesized through a modified hydrothermal process according to a previously reported protocol. 22 In a typical process, 5.4 mL of tetraethyl orthosilicate (TEOS, 99%) was dissolved in a solution of cyclohexane (50 mL, ≥99.5%) and n-pentanol (3.0 mL, ≥98.5% . Then, the mixture was placed in a Teflon-lined steel autoclave and heated at 120°C for 5 hours.…”
Section: Preparation Of D-ticual-sio 2 Nsmentioning
confidence: 99%
“…Dandelion-like silica was chosen to be the support of the catalyst because of its large specific surface area and unique fibrous structure, which could result in great exposure of the active component and significant accessibility for H 2 O 2 and pollutant molecules. 22 In the structure of this Fenton nano- connected with these metal atoms, a higher electron density was produced around Cu, while a lower electron density appeared in the region near Ti and Al, resulting in the formation of countless surface galvanic-like cells on the basis of the analysis of the extended X-ray absorption fine structure (EXAFS), X-ray photoelectron spectroscopy (XPS), Fouriertransform infrared spectroscopy (FTIR), electron paramagnetic resonance (EPR) and cyclic voltammetry (CV). Throughout the Fenton reaction, H 2 O 2 was always reduced to˙OH by the electrons around Cu, while the organic radical intermediates (˙R) from the degradation of organic pollutants, rather than H 2 O 2 , donated electrons to the electron-poor region, and these electrons were rapidly delivered to the Cu center due to the higher electronegativity of Cu, avoiding oxidation of H 2 O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Fenton catalysts based on DFNS were designed and synthesized by Lyu et al . The Fenton process is a powerful method to degrade pollutants in wastewater, although the stability of the catalysts has been an issue.…”
Section: Catalysis Using Dfnsmentioning
confidence: 99%